The Implementation Of Ananda's Ringing Program Based On Linking Books To Improve Grade 1 Learning Discipline - Sri Utami; M. Bambang Edi Siswanto (Prodi PGSD Fakultas Ilmu Pendidikan (FIP) Universitas Hasyim Asy'ari (Unhasy) Tebuireng Jombang, 2022)
This research is motivated by the lack of learning discipline of students at SDIT Ar Ruhul Jadid Jombang. Student learning discipline is formed from a good behavior that must be gradually and continuously applied. One of the implementations is to implement a link book-based ananda ring program. The objectives to be achieved in this research are to improve students' learning discipline through ananda ringing program based on connecting books, describe the form of student learning phenomena and describe how to grow student discipline at SDIT Ar Ruhul Jadid Jombang. This study uses a qualitative approach with a qualitative descriptive type of research. The subjects of this study were parents, classroom teachers and students. The data collection method used is the method of observation, interviews and documentation. The validity of the data was obtained by using source triangulation, time triangulation and technical triangulation. The results showed that; 1) Ananda ringing program based on the link book is able to improve the learning discipline of SDIT Ar Ruhul Jadid Jombang students. 2) Efforts to foster student learning discipline at SDIT Ar Ruhul Jadid is to use the Ananda ringing program which is supported by forming a TPDS (School Discipline Enforcement Team). 3) The form of student learning discipline can be seen from the increase in 3 aspects, namely; a) aspects of worship, b) social aspects, and c) aspects of independence.